Generation of Monoclonal Antibodies against Major Capsid Protein (MCP) of Nervous Necrosis Virus (NNV) - Chaivisuthangkura, Parin; Kamsamarn, Suphattra; Longyant, Siwaporn; Senapin, Saengchan; Vaniksampanna, Akapon; Manajit, Orapan (Science Essence Journal, 2023)
Viral encephalopathy and retinopathy (VER), a serious disease that affects several species of fish all over the world, is caused by nervous necrosis virus (NNV). In this study, two monoclonal antibodies (MAbs), namely 5C1 and 5C4, were generated from a mouse immunized with recombinant major capsid protein (MCP) of red-spotted grouper nervous necrosis virus (RGNNV). These MAbs displayed immunoreactivity against MCP and culture fluid of NNV-infected E-11 cell culture tested by dot blotting. Western blot analysis against recombinant MCP and the culture fluid of E-11 cells infected with NNV revealed immunoreactivity at approximately 63 and 37 kDa, respectively. Isotyping test revealed that all the MAbs were IgG2a. According to immunohistochemistry analysis, the MAbs immunoreactivities staining were found in viral assembly sites in the cytoplasm of targeted tissues such as gills and eye of NNV-infected Asian sea bass. The MAbs did not display any cross-reactivity with the recombinant capsid proteins of other fish viruses, including the infectious spleen and kidney necrosis virus (ISKNV), scale drop disease virus (SDDV), tilapia lake virus (TiLV), or other bacterial species commonly found in diseased fish. The immunoreactivity was observed when the MAbs were used for NNV detection by dot blotting in NNV-infected fish as verified by RT-PCR. These results indicated that the MAbs were useful in the development of more specific rapid and simple diagnostic technique for NNV infection in the future.